Eating Your Own Lunch: Protection Through Preemption - Nault, Barrie R.; Vandenbosch, Mark B. (Organization Science, 1996)
Recent discussions of management practices among successful high-technology companies suggest that one key strategy for success is to “eat your own lunch before someone else does.” The implication is that in intensely competitive, or hypercompetitive, markets, firms with a leading position should aggressively cannibalize their own current advantages with next-generation advantages before competitors step in to steal the market. Given the pace of technological and other types of change, such strategy often requires creating next-generation advantages while the current advantages are still profitable—that is, trading current profits for future market leadership. We capture the tradeoff between a market leader's willingness to reap profits with its current set of advantages and its desire to maintain market leadership by investing in the next generation. Using a competitive model that determines the equilibrium launch time of a next generation advantage, we find that, in absence of lower launch costs for an entrant, the incumbent will be first to launch to maintain its market leadership. That is, regardless of the severity of penalties for being a follower in the next generation, it is optimal for the incumbent to preempt the entrant by launching early—even if the incumbent consequently loses money at the margin. We derive a straightforward condition to determine when an incumbent will make negative incremental profits from its investment in the next-generation advantage. The fact that the condition does not depend on the size of the incumbent's investment costs indicates that the severity of competition, rather than the costs of developing and introducing a next-generation advantage, is what forces firms to cannibalize at a loss. Finally, we find that a preemptive launch can result in an earlier launch of the next generation than is socially optimal, and provide a sufficient condition for that to occur. Although customers are better off as a result of an earlier launch, their gain may be outweighed by the additional costs firms incur from launching prematurely.